Health shocks and spousal labor supply: An international perspective - Nicholas A. Jolly; Nikolaos Theodoropoulos (Global Labor Organization (GLO), 2022)
This paper uses data from the Survey of Health, Ageing and Retirement in Europe to analyze the effect of spousal health shocks on own labor supply decisions. Results from the analysis suggest minimal changes to the probability of work and the intensity of work for both husbands and wives of disabled spouses. Wives, however, do experience an increase in the probability of retirement after their husbands experience a work-limiting health shock. Results suggest that this increased probability is due to the desire to consume joint leisure. Finally, the analysis finds substantial cross-regional heterogeneity in the effect spousal health shocks have on the various labor market outcomes examined here, which suggests an important role for country-specific factors in the estimates provided in the earlier literature.
Keywords: I10; J12; J22; 330; health shocks; marriage; labor supply